The devil is in the detail: What do citizens mean when they support stealth or participatory democracy? - Fernández-Martínez, José Luis; Costa-Font, Joan (SAGE, 2017)
Recent research on citizen process preferences has highlighted three different models of decision making: representation, participation and stealth democracy. However, the meanings of the two alternatives to the prevailing representative model have not been fully explored. What do citizens have in mind when distinguishing between participatory and stealth models of democracy? Using survey data from several Western European countries, the article explores one distinction within preferences for each of the models: the preference for more referendum-based versus dynamic responsiveness-based solutions on the participatory side and for expert-based versus business-based solutions on the stealth side. The article ends by exploring the impact of left-right ideology and education upon these preferences. The explanatory power of the variables is greater for understanding the internal distinction of the stealth model than the participatory one.
https://openpolicyfinder.jisc.ac.uk/id/publication/7158
Keywords: Democracia directa; Education; Ideology; Participatory democracy; Stealth democracy; Process preferences